Favoring the Reactivity of TiO 2 Films with Ideal Arrangement of Anatase and Rutile Crystallites - Brandt, Iuri S.; Stroppa, Daniel G.; Lisboa-Filho, Paulo N. [UNESP]; Da Silva, José H. D. [UNESP]; Pasa, André A. (American Chemical Society (ACS), 2019)
It is shown that there are deposition conditions in reactive sputtering of TiO 2 in which the anatase and rutile crystals can coherently arrange in a convenient way that predominantly exposes the anatase facets, a configuration that is expected to favor the photocatalytic activity of the films. The latter process plays at present an important role in environmental conservation related to energy generation and water cleaning. Therefore, our results present an experimental path for obtaining highly photoreactive TiO 2 films.
Keywords: anatase; coherent growth; photocatalysis; reactive sputtering; rutile